Measurement of the transverse momentum and φ ∗ η distributions of Drell–Yan lepton pairs in proton–proton collisions at √s = 8 TeV with the ATLAS detector - Alconada Verzini, María Josefina (2016)
Distributions of transverse momentum pℓℓT and the related angular variable φ ∗ η of Drell–Yan lepton pairs are measured in 20.3 fb−1 of proton–proton collisions at √s = 8 TeV with the ATLAS detector at the LHC. Measurements in electron-pair and muon-pair final states are corrected for detector effects and combined. Compared to previous measurements in proton–proton collisions at √s = 7 TeV, these new measurements benefit from a larger data sample and improved control of systematic uncertainties. Measurements are performed in bins of lepton-pair mass above, around and below the Z-boson mass peak. The data are compared to predictions from perturbative and resummed QCD calculations. For values of φ ∗ η < 1 the predictions from the Monte Carlo generator ResBos are generally consistent with the data within the theoretical uncertainties. However, at larger values of φ ∗ η this is not the case. Monte Carlo generators based on the parton-shower approach are unable to describe the data over the full range of pℓℓT while the fixed-order prediction of Dynnlo falls below the data at high values of pℓℓT . ResBos and the parton-shower Monte Carlo generators provide a much better description of the evolution of the φ ∗ η and pℓℓT distributions as a function of lepton-pair mass and rapidity than the basic shape of the data.